2012
DOI: 10.1242/jcs.103093
|View full text |Cite|
|
Sign up to set email alerts
|

GRIM-19 Mediated Translocation of STAT3 to Mitochondria is Necessary for TNF Induced Necroptosis.

Abstract: SummaryTumor necrosis factor (TNF) can induce necroptosis, wherein inhibition of caspase activity prevents apoptosis but initiates an alternative programmed necrosis. The activity of receptor-interacting serine/threonine-protein kinase 1 (RIPK-1) is required for necroptosis to proceed, with suppression of RIPK-1 expression or inhibition of RIPK-1 activity with necrostatin-1 preventing TNF-induced necroptosis. Downstream from the TNF receptor, the generation of reactive oxygen species at the mitochondria has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 40 publications
3
88
1
Order By: Relevance
“…We demonstrated previously that during TNFa-induced necroptosis of L929 cells, the translocation of a complex of Stat3 and Grim-19 to the mitochondria occurs and brings about mitochondrial injury and loss of cell viability (Shulga and Pastorino, 2012). We wanted to determine whether a similar mechanism was applicable in TNFa-induced necroptosis of hepatocytes exposed to fructose and ethanol.…”
Section: Tnfa Induces Binding Of Stat3-grim-19 To Mitoneetmentioning
confidence: 98%
See 1 more Smart Citation
“…We demonstrated previously that during TNFa-induced necroptosis of L929 cells, the translocation of a complex of Stat3 and Grim-19 to the mitochondria occurs and brings about mitochondrial injury and loss of cell viability (Shulga and Pastorino, 2012). We wanted to determine whether a similar mechanism was applicable in TNFa-induced necroptosis of hepatocytes exposed to fructose and ethanol.…”
Section: Tnfa Induces Binding Of Stat3-grim-19 To Mitoneetmentioning
confidence: 98%
“…It has recently been demonstrated that RIPK-3 is required for ethanol induced liver injury (Roychowdhury et al, 2013). We have demonstrated that TNFa-induced necroptosis in some instances is brought about by RIPK-1-dependent phosphorylation of a STAT3-Grim-19 complex, which upon phosphorylation, translocates to the mitochondria where it induces production of reactive oxygen species (ROS) and onset of the transition to mitochondrial permeability (Shulga and Pastorino, 2012). However, how the STAT3-GRIM-19 complex induces ROS production at the mitochondria is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…During TNF-induced necroptosis, STAT3 undergoes Ser 727 phosphorylation, which is dependent on RIP1 expression and activation (37). Our previous reports (20,21) and the present study suggest that Y14 is involved in TNF-a-mediated signals through at least two possible mechanisms: enhancement of the association between TRADD and RIP1 and augmentation of NF-kB modification via STAT3.…”
Section: Discussionsupporting
confidence: 57%
“…Other biochemical activities that have been implicated in necroptotic cell death, including activation of phospholipase activity, 46 phosphorylation of signal transducer and activator of transcription 3 47 and mitochondrial membrane pore opening, regulated through cyclophilin D. 48 Very recently, involvement of cyclophilin D in necroptosis has been shown to be RIP3-dependent and that it can be inhibited by cyclosporin A. 49 This suggests that the neuroprotective effect provided by cyclosporin A that has been used previously to treat rats with diabetic retinopathy 50 and that can prevent the loss of therapeutic cell transplants from dying in the retina 51 could be in part the result of inhibiting RIP3-dependent necroptosis rather than due to its immunosuppressive activity alone.…”
Section: Discussionmentioning
confidence: 99%